Familial clustering of nasopharyngeal carcinoma in the family of an adolescent with nasopharyngeal carcinoma - Kara, Buket; Ertan, Kübra; Düzova, Mürsel; Çağlayan, Ahmet Okay; Köksal, Yavuz (The Turkish Journal of Pediatrics, 2022)
Background. Nasopharyngeal carcinoma (NPC) is one of the rare malignant diseases of childhood, of which only 1% occurs in children. In recent years, genetic factors have attracted attention in NPC. A very limited data have been reported about clustering within families. Case. Herein, the familial clustering of nasopharyngeal carcinoma in the family of an adolescent with nasopharyngeal carcinoma is presented. Conclusions. There is familial clustering in nasopharyngeal carcinoma (NPC), but our knowledge on this subject is limited, especially in children or adolescent populations. Therefore, we should be more careful in NPC in childhood, especially in first-degree relatives.